Facial fractures: a 1-year retrospective study in a hospital in Belo Horizonte Fraturas de face: um estudo retrospectivo de 1 ano em um hospital de Belo Horizonte - Bruno Ramos Chrcanovic; Belini Freire-Maia; Leandro Napier de Souza; Vasco de Oliveira Araújo; Mauro Henrique Nogueira Guimarães de Abreu (Sociedade Brasileira de Pesquisa Odontológica, 2004)
A retrospective study was performed to assess facial fractures in patients treated at a public hospital in Belo Horizonte, in 2000. The data collected included age, gender, etiology, distribution of maxillofacial trauma considering day of the week and month, anatomic site of the fracture, and treatment. The analyses involved descriptive statistics and chi-squared test, Bonferroni test and analysis of variance. A total of 1,326 facial fractures were found in 911 patients. Most fractures occurred in adults with age ranging from 21 to 30 years. Men were more affected than women, with a male-female ratio of 4.69:1. Accidents causing facial fractures occurred predominantly on weekends. Bicycle and motorcycle accidents were the major cause of trauma, followed by interpersonal violence, automobile accidents, and falls. When the relation between the gender and the etiology of facial fractures was analyzed, a significant relation was noted between these variables (p < 0.001). There was also a relation between the patients' age and the site of the fractures (p = 0.0014). The mandible was found to be the most commonly fractured bone in the facial skeleton, followed by the zygomatic complex and the nose. A non-surgical approach was chosen in most cases. There were significant differences between the kind of treatment applied and the site of the fracture (p < 0.001). Um estudo retrospectivo foi realizado para avaliar fraturas faciais em pacientes atendidos no ano de 2000 em um hospital público de Belo Horizonte. As informações coletadas incluíam idade, sexo, etiologia, distribuição do trauma de acordo com o dia da semana e o mês, o local anatômico da fratura e o tratamento. As análises envolveram estatísticas descritivas, teste qui-quadrado, teste Bonferroni e análise de variância. Foram encontradas 1.326 fraturas de face em 911 pacientes. A maioria das fraturas ocorreu em adultos na faixa etária de 21 a 30 anos. Os homens foram mais acometidos do que as mulheres, numa proporção homem:mulher de 4,69:1. Os traumas causadores de fraturas faciais ocorreram predominantemente nos fins de semana. Os acidentes de moto e bicicleta foram a maior causa de trauma, seguidos por violência interpessoal, acidentes automobilísticos e quedas. Quando analisada a relação entre o gênero e a etiologia das fraturas de face, observou-se uma associação estatisticamente significativa entre essas variáveis (p < 0,001). Houve também uma associação entre a idade dos pacientes e a localização das fraturas (p = 0,0014). O osso facial mais fraturado foi a mandíbula, seguida por complexo zigomático e nariz. O tratamento conservador foi realizado na maioria dos casos. Houve diferenças estatisticamente significativas entre o tipo de tratamento instituído e a localização da fratura (p < 0,001).